Seasonal variations in sleep of free-ranging Arabian oryx (Oryx leucoryx) under natural hyperarid conditions. Issue 5 (21st February 2018) - Davimes, Joshua G; Alagaili, Abdulaziz N; Bhagwandin, Adhil; Bertelsen, Mads F; Mohammed, Osama B; Bennett, Nigel C; Manger, Paul R; Gravett, Nadine
Abstract: Study Objectives: The Arabian oryx lives under hyperarid conditions in the Arabian Desert and exhibits temporal niche switching of activity patterns at a seasonal level. The objective of the current study was to provide a polysomnographic-based study of sleep in free-roaming Arabian oryx in their natural habitat to determine whether extreme seasonal climate variations resulted in changes in sleep patterns and physiology associated with the seasonal switching of temporal niches. Methods: Electroencephalography, nuchal electromyography, actigraphy, and subcutaneous temperature were recorded in free-roaming Arabian oryx in the Mahazat as-Sayd Protected Area, Kingdom of Saudi Arabia during winter and summer. Results: Total daily sleep time in winter was 6.69 and 3.77 hr in summer. In winter, oryx exhibited nocturnal sleep typical of artiodactyls of around 60 kg body mass. In summer, oryx slept mostly during the day and subcutaneous temperature was seen to rise during sleep, but not as rapidly as the rises observed in ambient air temperature. Rapid eye movement sleep formed a very small percentage of total sleep time, especially so in the summer. Conclusions: The unusual sleep patterns and physiology during summer appear to be related to high ambient air temperatures that affect both intrinsic and extrinsic factors necessary for survival. The Arabian oryx appears to use sleep physiology as an adaptive thermoregulatory mechanism in the hot summer months.